The untold story of the Mexican debt crisis: Domestic banks and external debt, 1977-1989 - Sebastian Alvarez (The European Association for Banking and Financial History (EABH), 2014)
In the years preceding the international debt crisis of the 1980s, international banks displayed a growing enthusiasm for lending to Mexico and other developing countries. During this period, Mexico's development and commercial banks got heavily involved in intermediating foreign finance with domestic final users. Although important, scholars have thus far neglected the role played by Mexican banks in international capital markets and in the country's external indebtedness process. This paper argues that the imbalances which Mexican banks incurred in running their international operations eventually brought them to the brink of bankruptcy once the crisis began. Given that the banks that were at risk represented a large share of the domestic market, this paper argues the whole Mexican banking system was threatened with collapse. The improved understanding of the banking system's exposure to and dependence on foreign finance provides new insights into Mexico's debt renegotiation outcomes and the nationalization of the banking system in the aftermath of the crisis.
Keywords: H63; N26; N86; 330; Sovereign debt; financial crisis; Euromarkets; Latin America